PS-BPB05-6: TOLVAPTAN INDUCES BODY FLUID LOSS AND ACTIVATION OF RENAL UREA-DRIVEN WATER CONSERVATION IN NORMAL RATS. (January 2023) - Kidoguchi, Satoshi; Kitada, Kento; Fujisawa, Yoshihide; Nakano, Daisuke; Yokoo, Takashi; Titze, Jens; Nishiyama, Akira
Abstract : Objective: We recently reported that body fluid loss models such as high salt-induced natriuresis, impaired urine concentration ability via kidney injury, and enhanced transepidermal water loss due to skin barrier dysfunction exhibit initial water loss and subsequent activation of the water conservation system in multiple organs. This activation of the water conservation system restores or even increases water content at the tissue level, which may be involved in abnormal body fluid distribution in various disease models. The water conservation system consists of renal urea recycling, the energy-intensive nature of hepato-muscular ureagenesis, and suppression of cardiovascular energy expenditure to save energy for ureagenesis. However, it is not clarified whether pharmacological fluid loss by diuretics activates the water conservation system. In this study, we examined the effects of water diuresis by tolvaptan, a selective vasopressin V2 receptor antagonist, on the water conservation system in normal rats. Design and method: 10-week-old male Sprague Dawley rats were fed with a control diet or a diet containing 0.1% tolvaptan. We measured water intake and urine volume for two weeks and also evaluated time-dependent changes in renal urea recycling and hepato-muscular ureagenesis in these rats. In addition, we also evaluated the effects of tolvaptan on blood pressure, heart rate, and renal sympathetic nerve activity by a radiotelemetry system in separate animals. Results: Tolvaptan markedly increased urine volume up to 126.7 ± 25.9 ml on day-1, which gradually decreased as much as one-third (48.1 ± 18.0 ml) on day-7. Tolvaptan significantly decreased body water content and increased plasma albumin concentration, an indicator of oncotic pressure, on day-1, suggesting that tolvaptan decreased body fluid and plasma volume on day-1. These changes in total body water content and plasma albumin concentration were restored on day-7. The restoration of body fluid on day-7 was associated with an increase in urea transporter A1-associated renal urea recycling. On the other hand, tolvaptan did not alter hepato-muscular ureagenesis or cardiovascular energy expenditure throughout the treatment. Conclusions: Tolvaptan induces initial body fluid loss by water diuresis and subsequent activation of renal urea recycling to restore the water loss. Activation of the water conservation system in addition to a rise in urine volume may be involved in the unknown distinct effect of the diuretics.